Faktor Risiko Pencemaran Mikrobiologi pada Air Minum Isi Ulang di Kabupaten Tegal - Rahayu, Cecilia Sri; Setiani, Onny; Nurjazuli, Nurjazuli (Jurnal Kesehatan Lingkungan Indonesia, 2013)
Background : Water is a real absolute necessity for humans as well as fresh air and healthy food. Result of inspection of drinking water refilling quality in Tegal Regency at 2011 showed the existence of microbiology contamination, from 138 drinking water refilling samples, in which 67 samples (48,6%) did not meet the standard for MPN Coliform and E.coli.The purpose this research was to know microbiological contamination risk factor of drinking water refilling in Tegal Regency. Methods : Design applied was cross-sectional. Independent variable in this research was standard water quality, quality of filtration, quality of desinfection and the dependent variable was water quality drinks product from drinking water refilling station. Population at this research was drinking water refilling station in Tegal Regency which amounts to 197. Sampling in random sampling that sample was taken in random. Test Chi-Square applied to test the relation of microbiology contamination risk factor of drinking water refilling with microbiology quality of product water from drinking water refilling station. Results : The result of inspection of standard water quality, 36 samples ( 55,4%) MPN ineligibility Coliform and 12 samples ( 18,5%) ineligibility Ecoli. Result of inspection of water quality drinks product DAMIU, 32 samples ( 49,2%) MPN ineligibility Coliform and 10 samples ( 15,4%) ineligibility Ecoli. Result of observation quality of filtration, 31 samples ( 47,7%) with quality of filtration is not good. Result of observation quality of desinfeksi, 28 samples ( 43,1%) with quality of desinfeksi is not good.The results of the research showed there was significant association between quality of water microbiology standard (p-value=0,0001), quality of filtration (p-value=0,0001), quality of desinfection (p-value=0,0001) with quality of product water microbiology in drinking water refilling station Tegal Regency at 2012. Product drinking water from drinking water refilling station using ineligible standard water of MPN coliform had risk 5,6 times compared to using standard water. Product drinking water from drinking water refilling station with quality of filtration that was not good had up risk 34 times compared to if the quality of filtration was good Product drinking water from drinking water refilling station with quality of desinfection which was not good had risk 9,2 times compared to if the good quality of desinfection. Recomendation :The owners of the drinking water refilling station was obliged to guarantee water quality to drink produced by it is safe for health. Public expected to be more attentively in consuming water product from drinking water refilling station. Health Department needs more increases construction and observation to drinking water refilling station. Keywords : Microbiological Contamination of Drinking Water Refilling,Tegal Regency